Aesthetics and Functionality of Graphic Design in Instagram Feed: Global Challenges and Opportunities - Wahyu Kurniawan; Della Naradika (Soshum: Jurnal Sosial dan Humaniora, 2026)
This study aims to explore the relationship and balance between aesthetic values and functional aspects in the context of graphic design on the Instagram platform, especially in the arrangement of user feeds. Through a qualitative approach by applying Miles and Huberman's analysis model, this study investigates how graphic designers integrate aesthetically appealing visual elements while maintaining functionality that optimises user experience and communication effectiveness. The data collection process was carried out through in-depth observation of Instagram feeds from various professional designers, accompanied by analysis of related documents and literature. The research findings show significant developments in the approach to Instagram feed design, where there is a dynamic balance between global trends and local adaptations. This study identifies innovative strategies used by designers to overcome the technical limitations of the Instagram platform, as well as optimise the visual potential to increase user engagement. The main contribution of this study lies in the development of a strategic framework for graphic design practitioners in maximising the aesthetic value and functionality in Instagram feeds. By understanding the dynamics of the interaction between these two aspects, designers can create visual content that is not only visually appealing but also effective in achieving communication goals in this competitive digital era.